Predatory capacity of Tupiocoris cucurbitaceus (Hemiptera Miridae) on several pests of tomato - Lopez, Silvia Noemi; Orozco Muñoz, Arlette; Andorno, Andrea Veronica; Cuello, Eliana Marina; Cagnotti, Cynthia Lorena (Department of Agroenvironmental Sciences and Technologies, Università di Bologna., 2023)
The predator Tupiocoris cucurbitaceus (Spinola) is frequently found preying on whiteflies in greenhouse tomato without pesticide use in Argentina. This study evaluated its preying capacity on several pests, determining the 24 hours consumption of females, males, large and small nymphs on nymphs of Bemisia tabaci (Gennadius), eggs and larvae of Tuta absoluta (Meyrick), nymphs of Myzus persicae (Sulzer) and Tetranychus urticae Koch females. Whitefly consumption varied between 15.7 and 38.2 nymphs/predator, the largest predation corresponding to the females of T. cucurbitaceus that also were most voracious of T. absoluta eggs (147.4) and M. persicae nymphs (19.8). T. cucurbitaceus individuals preyed 3.3 small larvae of T. absoluta while predation of large larvae was negligible for all predator stages. Finally, each predator consumed 27.8 T. urticae females. This information broadens our knowledge about the prey range and consumption capacity of this predator.